Prevalence of porcine cysticercosis and associated risk factors in Homa Bay District, Kenya - Eshitera, E.E.; Githigia, S.M.; Kitala, P.; Thomas, Lian F.; Fèvre, Eric M.; Harrison, L.J.; Mwihia, E.W.; Otieno, R.O.; Ojiambo, F.; Maingi, N. (Springer, 2012)
Taenia solium is an important zoonosis in many developing countries. Cysticercosis poses a serious public health risk and leads to economic losses to the pig production industry. Due to scarcity of data on the epidemiology of porcine cysticercosis in Kenya, the present study was conducted to determine the prevalence and risk factors for porcine cysticercosis within Homa Bay district. A cross-sectional survey was carried out in 2010, and a total of 392 pigs were recruited in a household survey, with all being tested by ante-mortem lingual palpation (together with questionnaire data on pig production, occurrence and transmission of porcine cysticercosis, risk factors and awareness of porcine cysticercosis collected from the households from which pigs were sampled). Sufficient serum was collected from 232 of the pigs to be tested for the presence of circulating parasite antigen using a monoclonal antibody-based sandwich enzyme-linked immunosorbent assay (Ag-ELISA). Results Seventy six pigs were found positive by the Ag-ELISA (32.8%, 95% C.I. 26.8-39.2%), while by tongue inspection cysticerci were detected in 22/ 392 pigs (5.6% 95% C.I. 3.6-8.4%). The most important risk factor for porcine cysticercosis in the Homa Bay area was for pigs to belong to a farm where latrine use by members of the household was not evident (OR = 1.9, 95% CI = 1.13–2.37). Conclusion The present findings indicate that porcine cysticercosis is endemic in Homa Bay District, and that latrine provision, in conjunction with free-range pig keeping contributes significantly to porcine cysticercosis transmission.